Florida 4-H Horse Member Advancement Program Level IV - Edward L. Johnson (EDIS)
This program is designed to help members understand principles of horse management and the application of these to their horses, help them develop a high degree of proficiency in horse handeling and horsemanship, allow them to participate in a broad range of 4-H Club experiences, and allow them to assist younger members.